Global Connectivity and Export Performance - Arvis, Jean-François; Shepherd, Ben (World Bank, Washington, DC, 2014)
The World Bank has developed a novel method for measuring countries connectivity in global networks and has applied it to the global air transport network. Connectivity in this context is defined as a country s relative position in that network in terms of the total push and pull it exerts on air traffic, taking account of all possible links with other countries. Well-connected countries that are strongly connected to other well-connected countries are considered hubs in this definition. Less well-connected countries are spokes. The Air Connectivity Index (ACI) shows that connectivity is highly concentrated in North America and Europe ( hubs ); most developing countries are relatively poorly connected ( spokes ). Developing countries looking to increase their participation in global value chains need to improve their connectivity as part of their overall competitiveness strategy, including the progressive liberalization of their air transport sectors.